Economic autarkeia: the legitimacy of the economic discourse based on the concept of physis - Zayas, María Florencia (Revista Archai, 2019)
The concept of autarkeia present in the Aristotelian Politics is conceived as inseparable from the end of the city-State, insofar as it is not only constituted for mere living (zen) but for living well (eu zen). This implies a moralization of the state order that allows us to think about the conformation of an economic dimension based on the concept of autarkeia. Taking as a methodological starting point the “dialogical tension zones” device (Mársico, 2010), we will affirm that exists an Aristotelian economic thinking based on three significant concepts of his political philosophy: “self-sufficiency”, “city-State”, “justice” (Polanyi, 1994). Finally, we will affirm that the concept of “natural slavery” aims to guarantee the constitution of an autonomous productive economic order that delegitimizes the federated states’ model of organization (summachia).